Co-solvent induced self-roughness superhydrophobic coatings with self-healing property for versatile oil-water separation - Gao, Shouwei (2019)
Despite of the extensive effort made to construct a superhydrophobic surface in labs, achieving a short processing time and via a sustainable production route remains a challenge for practical applications. Here, with tetrahydrofuran and n-hexane as co-solvent, we demonstrate that roughness can be induced on polydimethylsiloxane (PDMS) coatings to achieve superhydrophobic coatings on different types of substrates including woven fabrics, non-woven fabrics, and melamine sponge. The sample constructed without adding particles exhibited excellent performance for versatile oil-water separation of mixtures of heavy oil and water, light oil and water, as well as oil-water emulsion. Due to the good solubility of the PDMS in the co-solvent, the dipping solution exhibited a long-time stability. Moreover, the abundant CH3 provided by the self-roughness PDMS coating helped the substrates recover its superhydrophobic property even after destroyed by plasma for 10 times. We believe that this extremely easy dipping-curing method would open up a new direction for fabricating a series of self-roughed superhydrophobic surface with self-healing property. Besides, the developed strategy is fast and easily scalable for industrial applications.